Green Supply Chain Management (GSCM) Practices on Sustainability Performance in the Manufacturing Industry of Batam City - Syafrina, Mia; Dona, Rahma (Politeknik Negeri Batam, 2025)
The research aims to explore the effect of seven dimensions Green Supply Chain Management (GSCM) practices on three dimensions of sustainability performance, namely environmental, economic, and social. The seven dimensions of GSCM practices include green purchasing, green manufacturing, green marketing, green distribution and packaging, internal environmental management, environmental education, and investment recovery. The research sample was sourced from 70 manufacturing companies categorized as large and medium industries in Batam City. Data collection was done by distributing questionnaires. Data were statistically evaluated by applying Structural Equation Modeling-Partial Least Squares (SEM-PLS) methodology employing SmartPLS 4. Findings from the study indicate that every dimension of GSCM practice positively and significantly impacts on at least one dimension of sustainability performance. From seven dimensions of GSCM practices tested, green marketing and green distribution & packaging positively and significantly affect all three dimensions of sustainability performance.